Atomic resolution snapshot of Leishmania ribosome inhibition by the aminoglycoside paromomycin. Issue 1 (December 2017) - Shalev-Benami, Moran; Zhang, Yan; Rozenberg, Haim; Nobe, Yuko; Taoka, Masato; Matzov, Donna; Zimmerman, Ella; Bashan, Anat; Isobe, Toshiaki; Jaffe, Charles; Yonath, Ada; Skiniotis, Georgios
Abstract Leishmania is a single-celled eukaryotic parasite afflicting millions of humans worldwide, with current therapies limited to a poor selection of drugs that mostly target elements in the parasite's cell envelope. Here we determined the atomic resolution electron cryo-microscopy (cryo-EM) structure of theLeishmania ribosome in complex with paromomycin (PAR), a highly potent compound recently approved for treatment of the fatal visceral leishmaniasis (VL). The structure reveals the mechanism by which the drug induces its deleterious effects on the parasite. We further show that PAR interferes with several aspects of cytosolic translation, thus highlighting the cytosolic rather than the mitochondrial ribosome as the primary drug target. The results also highlight unique as well as conserved elements in the PAR-binding pocket that can serve as hotspots for the development of novel therapeutics. Leishmaniasis is a parasitic disease transmitted by the bite of infected sand flies. Here the authors describe an atomic resolution cryo-EM structure of theLeishmania ribosome in complex with the recently approved drug paromomycin (PAR) and highlight conserved elements in the drug binding pocket that mediate PAR deleterious effects on the parasite.